The Integration of SAP Software in Learning Accounting Information Systems to Face Industrial Revolution 4.0 - Asri Diah Susanti; Santoso Tri Hananto; Sri Murni (Assets: Jurnal Akuntansi dan Pendidikan, 2020)
ABSTRACTThis study aims to improve student competence by integrating SAP in the SIA course in the industrial revolution 4.0. This research is a classroom action research. Data analysis methods used are quantitative and qualitative. Qualitative analysis is done by identifying the weaknesses and strengths of the application of actions and analyzing critical points. Quantitative analysis was performed by paired sample t-test to strengthen the results of the study. The results showed that there was an increase in student competence from moderate to high in cycle 1. This result was also supported by the results of paired sample t-tests which showed that there was a difference in student competence before and after the integration of SAP in SIA courses.ABSTRAKPenelitian ini bertujuan untuk meningkatkan kompetensi mahasiswa dengan mengintegrasikan SAP dalam MK SIA dalam menghadapi revolusi industri 4.0. Penelitian ini merupakan penelitian tindakan kelas. Metode analisis data yang digunakan adalah kuantitatif dan kualitatif. Analisis kualitatif dilakukan dengan mengidentifikasi kelemahan dan kelebihan penerapan tindakan serta menganalisis titik kritis. Analisis kuantitatif dilakukan dengan paired sample t-test untuk memperkuat hasil penelitian. Hasil penelitian menjukkan bahwa terdapat peningkatan kompetensi mahasiswa dari sedang ke tinggi pada siklus 1. Hasil ini juga didukung oleh hasil paired sample t-test  yang menunjukan terdapat perbedaan kompetensi mahasiswa sebelum dan sesudah tindakan yaitu diintegrasikannya SAP dalam mata kuliah SIA.